Forecast Demand of Specialists with Higher Education for Russian Economy; Innovation Management and Education Excellence Vision 2020: from Regional Development Sustainability to Global Economic Growth - Chikov M. V. Mikhail Vladimirovich; Potekhina N. V. Nina Vasiljevna; Sannikova I. A. Inessa Anatoljevna; Shulinina Yu. I. Yuliya Igorevna (2016, 2016)
Title screen